Gratian, a Nicene and holy emperor: an identity built on the texts of Ambrose, bishop of Milan - Pohlmann, Janira Feliciano (Romanitas - Revista de Estudos Grecolatinos, 2020)
The purpose of this article is to analyze some elements built by Ambrose, bishop of Milan, to create a Christian identity based on the Council of Nicaea of 325, and at the same time identify Gratian as a “holy emperor” defender of this faith. To achieve this objective and to prove my hypothesis I analyze two works: De fide and De Spiritu Sancto. I note that both works were written by Ambrose between 378/380?-383 AD at the request of Augustus Gratian. It was a moment in which the Niceism asserted its notion of orthodoxy and the divine nature of the Roman emperor gained Christian aspects.